Simulating vehicle fleet composition: A review of system dynamics models. (November 2019) - Gómez Vilchez, Jonatan J.; Jochem, Patrick
Abstract: While the market evolution of electric vehicles is uncertain, numerous studies have explored the future market diffusion of this and alternative powertrain technologies. This paper reviews studies that are based on system dynamics models and classifies this literature into 'automotive industry-oriented' and 'public policy-oriented'. Our review shows that the models of most of these studies share basic properties by design, yet differ not only in purpose but also in the assumptions they adopt, particularly with regards to consumer choice of powertrains. Taken together, these diverse modelling exercises can be understood as a model library to gain insights into different key markets. In terms of the type of models examined, this paper also discusses some methodological issues and suggests future modelling developments. Further research needs include the interlinkage of models to better understand the evolution of the battery price. Highlights: A review of twelve system dynamics models sheds light into modelling alternative vehicle technology market uptake. To capture powertrain selection over time, discrete choice modelling frameworks tend to be present in the reviewed studies. Different numerical assumptions concerning the sales rate and learning rate were identified. No truly global system dynamics model representing electric vehicle market penetration was found.